Financial Infrastructure, Group Interests, and Capital Accumulation : Theory, Evidence, and Policy - Bossone, Biaggio (IMF Working Papers; Working Paper, 2003)
This study presents a theory of financial infrastructure - or the set of rules, institutions, and systems within which agents carry out financial transactions. It investigates the effects of financial infrastructure development on financial architecture and real capital accumulation, taking into account financial-sector special interests. It shows that a more developed infrastructure promotes financial market growth, reduces the scope of traditional banking, and helps investors make more efficient investment decisions. The theory presented explains why traditional banking predominates in the early stages of economic development and becomes relatively less important as the economy develops, and why banks may retard financial sector development. The study provides evidence in support of its predictions.